Using blogs, podcasts and google sites as educational tools in a teacher education program - Coutinho, Clara Pereira (2009)
Recent research shows that teachers´ familiarity, confidence and skills in integrating technology into the curriculum are dependent on the quality of training programs they attend. Aware of this context and responsible for preparing digitally wise teachers an ICT (Information Communication Technology) training program was implemented with a groups of 81 in-service teachers, who used different Web 2.0 tools - blogs, podcasts and GoogleSites - to design and create digital resources to use in the real classroom. In this article we describe the training experience, present and reflect on teachers´ feedback and discuss implications for the design of education programs.